2000
DOI: 10.1046/j.1442-200x.2000.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme gene insertion/deletion polymorphism and renal damage in childhood uropathies

Abstract: Our data suggest an association of D allele of the ACE gene insertion/deletion polymorphism and congenital urological abnormalities, which result in parenchymal damage in Kuwaiti Arab children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
2
8
0
4
Order By: Relevance
“…However, available reports gave conflicting results. In a study from Kuwait, an association has been found between this type of polymorphism in Kuwaiti Arab children with congenital urologic abnormalities including VUR and the occurrence of parenchymal renal damage [18].…”
Section: Discussionmentioning
confidence: 97%
“…However, available reports gave conflicting results. In a study from Kuwait, an association has been found between this type of polymorphism in Kuwaiti Arab children with congenital urologic abnormalities including VUR and the occurrence of parenchymal renal damage [18].…”
Section: Discussionmentioning
confidence: 97%
“…An ACE gene insertion-deletion (I/D) polymorphism has been shown to influence the circulating and cellular ACE concentration [14][15][16]. Its D allele is associated with a higher risk of developing a number of vascular disorders [17][18][19][20]. We have investigated the prevalence of ACE gene I/D polymorphism genotypes in premature Kuwaiti newborns to investigate their association with ROP and progression to advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin I-converting enzyme (ACE) is one of the most intensely studied candidate genes in human renal malformations (11)(12)(13). The insertion or deletion (I/D) of a 287-bp fragment in intron 16 of the ACE gene has proved to influence the activity of the renin-angiotensin system (14) and, therefore, the production of angiotensin II.…”
mentioning
confidence: 99%